Protestantismus und politische Partizipation: evangelische Parlamentarierinnen im Nachkriegsbayern zwischen Politik und Kirche - Haußmann, Annette; Spanos, Jonathan (Evangelische Theologie, 2019)
The article reflects on the interdependence of the political and ecclesial sphere and the influence of Protestant women in the first two decades after 1945. Two different biographies of women from Bavaria with active influence in politics and church and both members of the CSU, Elisabeth Nägelsbach (member of the Landtag) and Ingeborg Geisendörfer (member of the Bundestag), are taken into account concerning their self-understanding, their agenda setting and their rhetoric self-presentation. We argue, that the spheres of politics and church are interdependent and gender construction plays an important role. Furthermore, the developments in the ecclesial sphere took much longer and emancipation of women was implemented more hesitantly than in the political system. Also, theological arguments were crucial for this delay. The article suggests to consider a differentiated and context-sensible approach to understand the relationship between religious denomination and emancipation as well as the role of political conservative female politicians with an association to the church in the development of gender equalization.
Keywords: Protestantismus; Politik; Evangelisch-Lutherische Kirche in Bayern; Bayern; Geisendörfer, Ingeborg; Nägelsbach, Elisabeth